Comparative Analysis of Newspaper Framing of the Genres on Human Trafficking - Adeyeye, Josephine Osatohanmwen; Oboh, Godwin Ehiarekhian (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025DO - 10.58709/niujss.v11i4.2327, 2025)
The study examines ways in which the Nigerian newspapers often frame their reports and editorials on human trafficking. The objective was to clarify the media's narrative role in shaping public understanding and influencing policy discourse. The paper uses framing and priming model as its conceptual framework. The researchers used a sample comprising 346 Issues published by the Nigerian Guardian, Punch, and Vanguard to evaluate the manner in which the Nigerian newspapers often frame their reports on human trafficking. The findings revealed that the stories on human trafficking accounted for over 60% of the straight news stories published on trafficking in the period under review. The study noted the genres journalists used to frame the stories on trafficking tend to suggest to readers how they should interpret the stories on trafficking and meaning (what) they should infer from the stories on human trafficking, to underscore the fact that newspapers serve as both communication channels and ideological instruments. Consequently, the study advises the media to diversify their narrative forms beyond straightforward reporting by incorporating more features, editorials, and opinion articles to enrich contextual framing with a view to providing justice for the victims of human trafficking. Keywords: Human Trafficking, Media Framing, Policy Discourse, Advocacy, Nigerian Newspapers.